Integrasi AI Dalam Perencanaan Keuangan Berbasis Digital Untuk Meningkatkan Daya Saing Pada UMKM - Alan Smith Purba (CV. Multi Kreasi Media, 2024)
This community service aims to provide an understanding of financial planning using AI. The potential integration of artificial intelligence (AI) technology in digital financial planning to improve the competitiveness of MSMEs. This service program aims to provide training to MSME players in using AI-based financial planning applications, with a focus on cash flow analysis, financial projections, and financing optimization. Through the implementation of this technology, it is expected that MSMEs can manage their finances more effectively, strengthen their position in the market, and increase competitiveness in the digital economy.